Pengaruh Model Discovery Learning Terhadap Aktivitas dan Hasil Belajar Kognitif Peserta Didik - Oktriviani, Shella Oktriviani; Marpaung, Rini Rita; Yolida, Berti Yolida (FKIP Universitas Lampung, 2017)
The Effect of Discovery Learning Models on Activities and Students Cognitive Learning Outcomes. This study aims to determine the effect of discovery learning on activities and cognitive learning outcomes students of class VIII SMPN 1 Lawang Kidul in